An Investigation Into the Perceptions of Teachers and Students in Mexico on the Implementation of Secondary Reforms. Issue 2 (April 2022) - Joong, Yee Han Peter
This mixed methods study examines how secondary school teachers have implemented educational reforms in Mexico. Major sources of data were surveys from sample teachers and students in 12 schools on how often a teaching or evaluation strategy was used. Results from open-ended questions and classroom observations were used to triangulate results from survey data. The study concluded that most teachers were able to adopt majority of the reforms. Even though teacher-directed lessons still dominated, student-centered learnings were incorporated. However, classroom management need increased attention due to new challenges of transitioning. Educators in all jurisdictions can learn from the reform efforts.